The Context Effect in the Significance of Sources and Derivatives Buildings in the Fadak Writings - Wahhab, Alaa Shafeeq (Al-Adab Journal, 2019)
In this study, we discussed the effect of the context on the significance of the sources and derivatives in the Fadak sermon to achieve the meaningful meaning of this approach. The context has a great impact on the production of significance through the availability of verbal and moral evidence. The nature of the study required that it be organized into three pre-existing studies. The second topic was devoted to the linguistic differences between the buildings of names, including the buildings of sources, the derivatives structures (the name of the actor and the name of the verb). The third topic dealt with the semantic diversity of morphological formulas. The context has an impact on the direction of the meaning of the morphological structure. In Arabic, these buildings did not exist arbitrarily, but there are advantages that we can perceive by employing them in context.